2007
DOI: 10.1007/s00221-007-1091-0
|View full text |Cite
|
Sign up to set email alerts
|

TMS of the occipital cortex induces tactile sensations in the fingers of blind Braille readers

Abstract: Various non-visual inputs produce cross-modal responses in the visual cortex of early blind subjects. In order to determine the qualitative experience associated with these occipital activations, we systematically stimulated the entire occipital cortex using single pulse transcranial magnetic stimulation (TMS) in early blind subjects and in blindfolded seeing controls. Whereas blindfolded seeing controls reported only phosphenes following occipital cortex stimulation, some of the blind subjects reported tactil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(57 citation statements)
references
References 47 publications
2
53
0
1
Order By: Relevance
“…This happens in blindfolded sighted participants (Merabet et al, 2007(Merabet et al, , 2008 and blind participants (Sadato et al, 1996(Sadato et al, , 1998(Sadato et al, , 2002(Sadato et al, , 2004Cohen et al, 1999;Burton et al, 2002Burton et al, , 2006Ptito et al, 2005;Stilla et al, 2008). Several lines of evidence suggest a functional role for cross-modal plasticity: a congenitally blind Braille reader developed alexia for Braille after suffering a bilateral occipital stroke , occipital transcranial magnetic stimulation (TMS) impairs blind participants' tactile performance (Cohen et al, 1997(Cohen et al, , 1999Kupers et al, 2007), and occipital TMS elicits sensations on the fingers in some participants (Ptito et al, 2008).…”
Section: Possible Neural Mechanismsmentioning
confidence: 99%
“…This happens in blindfolded sighted participants (Merabet et al, 2007(Merabet et al, , 2008 and blind participants (Sadato et al, 1996(Sadato et al, , 1998(Sadato et al, , 2002(Sadato et al, , 2004Cohen et al, 1999;Burton et al, 2002Burton et al, , 2006Ptito et al, 2005;Stilla et al, 2008). Several lines of evidence suggest a functional role for cross-modal plasticity: a congenitally blind Braille reader developed alexia for Braille after suffering a bilateral occipital stroke , occipital transcranial magnetic stimulation (TMS) impairs blind participants' tactile performance (Cohen et al, 1997(Cohen et al, , 1999Kupers et al, 2007), and occipital TMS elicits sensations on the fingers in some participants (Ptito et al, 2008).…”
Section: Possible Neural Mechanismsmentioning
confidence: 99%
“…In blind subjects visual cortex TMS interferes with both Braille reading and general tactile perception (Zangaladze et al, 1999;Kupers et al, 2007). However, it is difficult to compare studies using blind subjects to those using sighted subjects, as visual cortex in blind subjects is often sensitive to inputs from other modalities (Ptito et al, 2008).…”
Section: Comparison To Prior Workmentioning
confidence: 99%
“…The authors concluded that the subjective character of the percept would depend on the stimulated sensory channel and not on the activated cortex. In other words, according to these authors, the subjective experience associated with an activity in the visual cortex after sensory remapping is tactile and not visual (see also Ptito et al, 2008).…”
Section: Activation Of the Associated Brain Areasmentioning
confidence: 99%